2021
DOI: 10.3390/jcm11010113
|View full text |Cite
|
Sign up to set email alerts
|

Are Markers of Allergic Inflammation in Grass Pollen Allergy Influenced by H1 Antihistamines?

Abstract: Soluble intercellular adhesion molecule-1 (ICAM-1) and soluble vascular adhesion molecule-1 (VCAM-1) play important roles in allergic rhinitis (AR). Treatment with H1 antihistamines improves AR symptoms and in vitro reduces the levels of adhesion molecules. The aim of the study was to evaluate serum levels of ICAM-1 and VCAM-1 in patients with AR to grass pollen and their response to different H1 antihistamines. Material and methods: A total of 50 patients with grass pollen AR were clinically and biologically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…It acts by enhancing the aggregation of neutrophils. When it is activated, it causes accumulation of inflammatory and immune effector cells in addition to its action on T cells in the immune response, leading to potentiation of the release of cytokines (Bocsan et al 2021). Results showed that the effect of treatment on inhibition of the Ilβ4 level were in the order of O1 > BO > D4.…”
Section: Effect Of Different Formulations On Inflammatory and Allergi...mentioning
confidence: 99%
See 1 more Smart Citation
“…It acts by enhancing the aggregation of neutrophils. When it is activated, it causes accumulation of inflammatory and immune effector cells in addition to its action on T cells in the immune response, leading to potentiation of the release of cytokines (Bocsan et al 2021). Results showed that the effect of treatment on inhibition of the Ilβ4 level were in the order of O1 > BO > D4.…”
Section: Effect Of Different Formulations On Inflammatory and Allergi...mentioning
confidence: 99%
“…Results obtained on treatment with DEX salt can be explained in light of the study of Bocsan et al, who revealed that ICAM-1 levels were greater in patients sensitized with pollen grains and suffering allergic rhinitis, than non-sensitized individuals during pollen exposure. On the other hand, treatment with antihistaminic therapy didn't lower their levels in sera during pollen season (Bocsan et al 2021). In a related investigation, Vestbo and associates prospectively tracked 290 individuals with mild to moderate chronic obstructive pulmonary disease (COPD) and discovered no variation in the pace of inflammatory mediator decrease.…”
Section: Effect Of Different Formulations On Inflammatory and Allergi...mentioning
confidence: 99%